The Effect of Liquidity and Leverage on Profitability of Property and Real Estate Company in Indonesian Stock Exchange - Rudin, M.; Nurdin, Djayani; Fattah, Vita Yanti (International Journal of Social Sciences and Management, 2016)
The objectives of this research were to know and analyze the effect of leverage and liquidity simultaneously and partially on profitability at go public real estate and property company in Indonesian stock exchange within the period of 2005 until 2010. In detail, this research aims were: 1) to know the effect of liquidity and leverage on profitability of property and real estate company in Indonesian stock exchange, 2) to know the effect of liquidity on profitability of property and real estate company in Indonesian stock exchange, and 3) to know the effect of leverage on profitability of property and real estate company in Indonesian stock exchange. Based on purposive sampling technique, this research determined 43 companies as research population, since 16 companies provide a comprehensive and complete financial report within the period of research. The data was analyzed using SPSS version 16 with multiple linear regression test. The result showed that: 1) leverage and liquidity simultaneously have significant effect on profitability, 2) liquidity have an effect partially on profitability, but the effect was not significant, 3) leverage have a significant effect on profitability partially.Int. J. Soc. Sc. Manage. Vol. 3, Issue-4: 300-304